Synthesis and Antifungal Activity of 3,5-Disubstituted Phenyl Imino-1,2,4-Triazoles - A Siddiqui, Anees; Ul Islam, Mojahid; Siddiqui, Nadeem (Asian Journal of Chemistry, 2010)
A series of new triazoles have been synthesized and evaluated for antifungal activity against Candida albicans.